The national interest in question : foreign policy in multicultural societies - Hill, Christopher, 1948- (Oxford : Oxford University Press, 2013)
This volume examines the interaction between foreign policy-making and multicultural societies. It analyses the challenges of rapid social change associated with inward migration and increased ethnic and cultural diversity in ten EU Member States.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on August 26, 2013).
Keywords: International relations and culture -- European Union countries; Cultural pluralism -- European Union countries; European Union countries -- Foreign relations